2015
DOI: 10.1021/acs.jpcc.5b09571
|View full text |Cite
|
Sign up to set email alerts
|

An Adsorption Study of CH4 on ZSM-5, MOR, and ZSM-12 Zeolites

Abstract: CH 4 adsorption was studied experimentally and theoretically on ZSM-5, MOR, and ZSM-12 zeolites using calorimetric measurements at 195 K and plane wave DFT calculations. Differential heats measured on four different H-ZSM-5 samples were determined to be 22.5 ± 1 kJ/mol, independent of Brønsted site density or defect concentration. However, DFT calculations performed using various functionals and on the most stable Brønsted site indicated that CH 4 should bind to this site by an additional 1−7 kJ/mol, a discrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…An important example is that of simple alkanes wherein the adsorption thermochemistry depends on the dispersive interactions with the zeolite wall and the noncovalent interactions with the acid site. In our previous study, we showed that interactions of CH 4 with the Brønsted sites in H-ZSM-5 do not contribute significantly to the heats of adsorption; differential heats were found to be independent of coverage or zeolite Si/Al 2 ratio. However, there are both experimental , and theoretical , reports that the contributions to the heats of adsorption from interactions with Brønsted sites are significant for larger alkanes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…An important example is that of simple alkanes wherein the adsorption thermochemistry depends on the dispersive interactions with the zeolite wall and the noncovalent interactions with the acid site. In our previous study, we showed that interactions of CH 4 with the Brønsted sites in H-ZSM-5 do not contribute significantly to the heats of adsorption; differential heats were found to be independent of coverage or zeolite Si/Al 2 ratio. However, there are both experimental , and theoretical , reports that the contributions to the heats of adsorption from interactions with Brønsted sites are significant for larger alkanes.…”
Section: Introductionmentioning
confidence: 85%
“…Finally, most real zeolites have significant concentrations of vacancy defects, observable as nested silanols; and these have a profound effect on the adsorption of polar molecules, like water . Although vacancy sites do not appear to affect CH 4 adsorption, CH 4 adsorption was also not affected by the presence of Brønsted sites.…”
Section: Introductionmentioning
confidence: 98%
“…At lower temperatures, such as 195 K, the partition function occupancy is more separated by the different adsorption sites, allowing one to distinguish the adsorption energy associated with each type of site. [56][57][58][59][60] Measurements at higher temperatures (293 K) typically represent some average binding enthalpy from the different adsorption sites in the MOF and complicate the analysis. In fact, partition-function occupancyprobability calculations suggest that it is likely impossible to observe minority adsorption site enthalpies that are 5 kJ/mol higher than the majority adsorption sites at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To that endeavor, precise characterization of the adsorption sites and the determination of the gas-solid interaction modes and corresponding interaction energy are prime requirements. Moreover, a similar strategy can also be used in the search for cost-effective adsorbents for large-scale (reversible) storage and delivery of fuels such as methane and hydrogen; which constitutes a present-day strategic issue in the transportation sector [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Aside from the foregoing usage, increased knowledge of the nature and layout of active adsorption sites is also highly relevant to the wide-ranging industrial application of zeolites as catalysts in several fields, such as the petrochemical industry, methanol to olefin conversion, catalytic production of specialty chemicals [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and CO 2 methanation [ 28 , 29 ], to mention only a few examples.…”
Section: Introductionmentioning
confidence: 99%